Flow Characteristics of Skimming Regime Flow over Stepped Spillways with Attention to Optimum Step Size - Salmasi , Farzin; Abraham , John (Current Overview on Science and Technology Research Vol. 6, 2022)
On a spillway chute, a stepped design increases the rate of energy dissipation on the chute itself and reduces the size of the downstream energy dissipater. A study was conducted herein to gain a better understanding of the flow behavior in stepped chutes with a skimming flow. The work used a wide variety experimental facilities and large-size models obtained previously by other researchers. The present results yield a new and practical design procedure for stepped spillways with skimming flow. The design method includes some key issues not foreseen in prior studies. The outcomes are valid for a wide range of chute geometries and flow conditions typical of embankment chutes. Hydraulic-design charts for a stepped channel are provided. From these charts, the optimum number of step for maximum energy dissipation is determined that can reduce the size of a downstream energy dissipater. This procedure is easy to implement for designers provided parameters such as the optimum number of steps for maximum energy dissipation, the representative flow depth, the averaged velocity at the end of the stepped channel, height of the sidewall, and stilling basin type.